Rancang Bangun Cooler Box Portebel Menggunakan 2 Modul Peltier Tec1 - 12715 Dengan Suplai Daya 12 Volt 20 Ampere - M. Lugas Syahrani Faqih; Muhammad Halil; Een Tonadi (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study discusses the design of a portable cooler box based on a thermoelectric cooling system using two Peltier TEC1-12715 modules with a 12 Volt 20 Ampere power source. The use of Peltier modules was chosen because it has a simple construction, does not use refrigerants, and is more environmentally friendly than conventional cooling systems. This study aims to understand the expertise of the cooling system in reducing the temperature of the cooling room through static and dynamic testing. The method used is an experimental method by designing tools, assembling the cooling system, and testing the performance of the tool. Static testing is carried out without a cooling load, while dynamic testing is carried out using a load as a simulation of actual working conditions. The parameters observed include changes in temperature, voltage, current, and electrical power during the testing process. Based on the results, it provides an explanation that in static conditions the temperature of the cooling room can drop from 30°C to 21°C in 60 minutes. The fastest temperature decrease occurs at the beginning of the test, namely from 30°C to 22.7°C in 8 minutes, then the temperature decreases slowly until it reaches a stable condition in the range of 21–21.4°C. In dynamic testing, the temperature of the cooling chamber dropped from 30°C to 23°C within 60 minutes. During the testing process, the electrical voltage was in the range of 209–216 Volts, the electrical current was 1.7–2.2 Amperes, and the electrical power ranged from 250–266 Watts. Based on the research results, the Peltier module-based cooling system was able to work well in reducing the temperature of the cooling chamber gradually and stably, with relatively constant power consumption and has the potential as an alternative portable cooling system that is practical and environmentally friendly.